Role of Bone Marrow-Derived Stem Cells in Polyps Development in Mice with ApcMin/+ Mutation - Michele Barone; Maria Principia Scavo; Raffaele Licinio; Michele Piombino; Nicola De Tullio; Rosanna Mallamaci; Alfredo Di Leo (Stem Cells International)
We explored the hypothesis that an altered microenvironment (intestinal adenomatous polyp) could modify the differentiation program of bone marrow-derived stem cells (BMSCs), involving them in colon carcinogenesis. Sublethally irradiated 8-week-old female ApcMin/+ mice were transplanted with bone marrow (BM) cells obtained from either male age-matched ApcMin/+ (Apc-Tx-Apc) or wild type (WT) (WT-Tx-Apc) mice. At 4 and 7 weeks after transplantation, BM-derived colonocytes were recognized by colocalization of Y-chromosome and Cdx2 protein (specific colonocyte marker). Polyp number, volume, and grade of dysplasia were not influenced by irradiation/transplantation procedures since they were similar in both untreated female ApcMin/+ and Apc-Tx-Apc mice. At 4 and 7 weeks after transplantation, a progressive significant reduction of polyp number and volume was observed in WT-Tx-Apc mice. Moreover, the number of WT-Tx-Apc mice with a high-grade dysplastic polyps significantly decreased as compared to Apc-Tx-Apc mice. Finally, at 4 and 7 weeks after transplantation, WT-Tx-Apc mice showed a progressive significant increase of Y+/Cdx2+ cells in “normal” mucosa, whereas, in the adenomatous tissue, Y+/Cdx2+ cells remained substantially unvaried. Our findings demonstrate that WT BMSCs do not participate in polyp development but rather inhibit their growth. The substitution of genotypically altered colonocytes with Y+/Cdx2+ cells probably contributes to this process.